Unintentional rapid opioid detoxification - Singh, Shubh M. (Array, 2009)
Naltrexone is a competitive opioid antagonist and is often used to maintain abstinence in detoxified opioid dependent patients. However, it can precipitate an accelerated withdrawal when ingested by an individual with concurrent opioid use. We report the case of a 28 year old male with opioid dependence syndrome presenting with chaotic symptoms following ingestion of naltrexone. Symptomatology, management is described and literature in this area is reviewed. Accidental or surreptitious ingestion of naltrexone in a patient with concurrent opioid use can precipitate symptoms typical of opioid withdrawal in addition to other varying symptomatology. Most cases would require sedation and management of concurrent vomiting and diarrhoea